The Impact of Non-mandatory Police Reporting on Domestic Violence - Esther Arenas-Arroyo (Institute of Labor Economics (IZA), 2025)
Can lowering barriers to public services reduce domestic violence? Exploiting the introduction of a non-mandatory police reporting policy, I find that it significantly reduces domestic violence cases reported to the police while increasing hospital-reported cases of domestic assault. I further show that non-mandatory reporting laws reduce fatal domestic violence cases by facilitating the dissolution of abusive relationships and decreasing violence within intact couples. These findings highlight the importance of alternative support systems in addressing domestic violence.
Keywords: J12; J78; H76; 330; domestic violence; intimate partner homicide; criminal justice